Digital Transformation of Local Language, Literature, and Culture in the Era of Society 5.0 - Nurjanah, Nunuy; Srihilmawati, Rostika; Muntako, Berian (CV. Goresan Pena, 2025)
Indonesia’s linguistic and cultural diversity is seriously threatened due to globalization, technological acceleration, and the declining intergenerational transmission of local languages. This study explores the strategic role of digital transformation in preserving local language, literature, and culture within the framework of Society 5.0. Using a qualitative descriptive approach, the paper analyzes various digital initiatives—such as educational websites, mobile applications, and multimedia content—as tools for revitalization and dissemination. Results show that digital platforms support documentation and access and strengthen literacy, 21st-century competencies (5C), and cultural identity among younger generations. Furthermore, the research highlights the importance of multisector collaboration and community-based sustainability models to overcome challenges such as limited digital infrastructure, lack of linguistic documentation, and human resource constraints. Digitalization thus emerges not merely as a technological adaptation, but as a transformative movement for cultural resilience, innovation, and global relevance. The findings offer a framework for integrating local heritage into the future digital ecosystem.